2011
DOI: 10.1016/j.addbeh.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of hallucinogen and inhalant/solvent abuse and dependence criteria: Implications for the diagnostic and statistical manual of mental disorders—Fifth edition

Abstract: Background Prior research has demonstrated the dimensionality of Diagnostic and Statistical Manual of Mental Disorders - Fourth Edition (DSM-IV) alcohol, nicotine, cannabis, cocaine and amphetamine abuse and dependence criteria. The purpose of this study was to examine the dimensionality of hallucinogen and inhalant/solvent abuse and dependence criteria. In addition, we assessed the impact of elimination of the legal problems abuse criterion on the information value of the aggregate abuse and dependence criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
3
21
0
1
Order By: Relevance
“…Other studies using LCA agree that classes represent a continuum of severity [5,24,25,42]. Results of other recent studies on opioids [9,10,14], alcohol [7,8,10,29,31,32,33,41], cannabis [9,10,11,12,13], nicotine [16,38], and other addictive substances [9,17,18] are in agreement with this finding. In addition, the association of history of treatment for OUD in the past 12 months with the resulting classification by LCA showed the validity of the classification.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Other studies using LCA agree that classes represent a continuum of severity [5,24,25,42]. Results of other recent studies on opioids [9,10,14], alcohol [7,8,10,29,31,32,33,41], cannabis [9,10,11,12,13], nicotine [16,38], and other addictive substances [9,17,18] are in agreement with this finding. In addition, the association of history of treatment for OUD in the past 12 months with the resulting classification by LCA showed the validity of the classification.…”
Section: Discussionmentioning
confidence: 51%
“…Results of some older studies demonstrated that abuse and dependence criteria are distinct and show two different aspects [3,4,5,6]. However, recent studies on consumers of alcohol [7,8], cannabis [9,10,11,12,13], opioids [9,10,14], nicotine [15,16], and other addictive substances [9,17,18] suggest one aspect for both.…”
Section: Introductionmentioning
confidence: 99%
“…The following socio-demographic correlates were considered: gender, age (categorized as [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and 55 years or more); education (0-4, 5-8, 9-11, 12 years or more, respectively defined as low, low-average, high-average, and high); marital status (married/cohabiting, previously married [separated/divorced/widowed], never married); employment (working/student, homemaker, retired, unemployed/other);…”
Section: Sociodemographic Variablesmentioning
confidence: 99%
“…Isso aproxima o conceito de TUT dos conceitos de transtorno do uso de álcool (Preuss et al, 2013), maconha , estimulantes , opioides (CastaldelliMaia et al, 2016), sedativos/tranqüilizantes , alucinógenos (Kerridge et al, 2011), e inalantes . No entanto, poucos estudos têm explorado a dimensionalidade da dependência do tabaco através de critérios tanto do DSM-IV como da CID-10 , especialmente fora dos países de alta renda.…”
unclassified
See 1 more Smart Citation